Anxiety disorders and mood disorders in hospital doctors: a literature review - Richard Pougnet; Laurence Pougnet (Nofer Institute of Occupational Medicine, 2021)
This paper is focused on mental health among hospital doctors. This is a review of the literature dated January 1, 2005-December 31, 2019, from the MedLine and Scopus databases. The prevalence of post-traumatic stress disorder and anxiety disorders ranged 2.2-14.6% and 10.5-19.3%, respectively. Several risk factors were significant, such as having had blood exposure accidents, or the interaction between family and work life. The prevalence of mood disorders ranged 7.8-48%. Occupational constraints, such as night work or psychological demand, were related to the presence of mood disorders. This literature review showed the prevalence of disorders that can be reactive at work in hospital doctors. The risk factors studied can guide prevention policies within hospitals. Med Pr. 2021;72(2):163-71